GOVERNANCE AND ACCOUNTABILITY OF SPECIAL AUTONOMY FUNDS : EVIDENCE FROM ACEH, INDONESIA - Mukhtaruddin (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2025)
This study investigates the governance and accountability of Special Autonomy Funds (SAF) in Aceh, Indonesia, a post-conflict region with significant fiscal transfers following the 2005 Helsinki peace agreement. Using a mixed-methods design, combining interviews, focus groups, surveys, and secondary data analysis, the research examines institutional frameworks, implementation outcomes, and the role of civil society in fund oversight. Findings reveal persistent weaknesses in governance structures, including overlapping institutional mandates, limited regulatory enforcement, and political interference that undermines alignment between policy objectives and development outcomes. Quantitative evidence indicates that nearly 30% of SAF-funded projects failed to achieve intended goals, while qualitative insights highlight exclusion of civil society organizations from decision-making processes, contributing to weak accountability. Nevertheless, case studies of participatory initiatives in health and environmental programs demonstrate the potential of inclusive governance and digital monitoring to improve transparency and citizen trust. This study contributes to the literature on public financial management by emphasizing the importance of context-specific approaches to governance in post-conflict regions. It underscores the necessity of strengthening legal frameworks, clarifying institutional responsibilities, and fostering civil society engagement. The findings provide both theoretical insights into accountability mechanisms and practical recommendations for policymakers seeking to enhance the effectiveness of special fiscal transfers in decentralized systems.